Viral Infections Associated with Anemia - Azimi, Seyed Gholamreza; Goudarzi, Hossein; Faghihloo, Ebrahim (Novelty in Biomedicine, 2025)
Background: Anemia is a serious blood disorder characterized by the bone marrow’s inability to produce new blood cells, which can be either acquired or inherited. Exposure to viral infections can lead to anemia, including diseases caused by parvovirus B19, Epstein-Barr virus, cytomegalovirus, human immunodeficiency virus, hepatitis C virus, varicella-zoster virus, and SARS-CoV-2. While these infections are often subclinical in immunocompetent individuals, they can become critical and cause anemia in high-risk populations, such as immunocompromised individuals or those with underlying conditions like sickle cell disease, particularly in infants and pregnant women. Materials and Methods: The search was performed using PubMed and Google Scholar for articles published from 2000 to 2024.The primary search string was: ("anemia" OR "erythroid aplasia") AND ("virus" OR "viral infection"), "Parvovirus B19", "Human Immunodeficiency Virus" OR "HIV", "Hepatitis C Virus" OR "HCV", "SARS-CoV-2" OR "COVID-19", "Varicella-Zoster Virus" OR "VZV", "Cytomegalovirus" OR "CMV", and "Epstein-Barr Virus" OR "EBV". Results: Viral infections are important causes of anemia, through various mechanisms. Parvovirus B19 causes aplastic anemia by targeting red blood cell precursors, while HIV leads to anemia through chronic disease. Hepatitis C causes anemia via bone marrow suppression. SARS-CoV-2 disrupts iron metabolism through inflammation. Other viruses like CMV mainly cause anemia in immunocompromised patients. Conclusion: This article aims to review the evidence regarding virus-induced anemia, detailing mechanisms such as erythroid progenitor cytotoxicity, chronic inflammation, and treatment-related haemolysis. Diagnostic strategies, ranging from serological assays to pathognomonic bone marrow findings, are discussed to assist laboratory science professionals and clinical specialists in diagnosing, treating, and managing patients with anemia.